Mosquito (Diptera: Culicidae) fauna of the Velyka Dobron' Game Reserve (West Ukraine) with new distribution data and medical risk assessment - Szanyi Kálmán; Nagy Antal; Molnár Attila; Молнар Атілла; Szabó László József; Szanyi Szabolcs (The Scientific and Technological Research Council of Turkey, 2020)
Abstract. The distribution of mosquito species in the Transcarpathian part of Ukraine is poorly studied. Here we present the results of a four-year survey carried out in the Velyka Dobron’ Game Reserve, and provide the actualized checklist of the Transcarpathian Culicidae fauna containing 32 species. Four of the sampled species have not been formerly known in Transcarpathia: Anopheles hyrcanus, Ochlerotatus cataphylla, Ochlerotatus nigrinus, Uranotaenia unguiculata. Based on quantitative composition of studied assemblage, vector potential of species and distribution of transmitted pathogens we evaluate the medical and veterinary risk caused by mosquitoes in Transcarpathian region.
Keywords: Ukraine; vector; infection risk; Anopheles; Ochlerotatus